Alterations in the junctions between brain endothelial cells and pericytes during chronic sleep restriction - Medina Flores, María Fernanda (Universidad Autónoma Metropolitana, 2019)
Sleep loss produces blood-brain barrier (BBB) hyperpermeability by increasing endocytosis and promoting tight junction disassemble. Similar effects have been reported in mice with pericyte deficiency. In previous studies, we showed that pericytes seem to detach from the capillary wall in sleep-restricted animals. Thus, we aimed to evaluate the changes in brain endothelial cell-pericyte interactions and its consequences on barrier function during sleep restriction. Male Wistar rats were subjected to sleep loss using the multiple platform technique for 20 h daily during 10 consecutive days. After 10 days of sleep loss, animals were euthanized, and the brain was removed to isolate brain microvessels from the cerebral cortex and hippocampus. The samples were used to evaluate the expression of PDGFRβ, connexin-43, claudin-5, occludin, MMP-9, NFkB, p-NFkB, A2A adenosine receptor and CD73 by Western blot. An immunofluorescent assay was made for PDGFRβ or connexin-43 in isolated brain microvessels from the cerebral cortex and hippocampus. Another group of rats was used to perform BBB permeability assays to Na-fluorescein, Evans blue and rhodamine 123. In isolated blood-microvessels of the cerebral cortex and hippocampus, sleep restriction reduced PDGFRβ expression in comparison with the control group. Likely, sleep restriction reduced the expression of connexin-43 in the cerebral cortex; meanwhile, in the hippocampus there was a trend to reduce connexin-43 expression compared to the control group. Sleep loss decreased the expression of claudin-5 in the isolated microvessels only in the cerebral cortex, while it decreased occludin expression in the hippocampus but not in the cerebral cortex as compared to the intact group. Sleep restriction increased MMP-9 expression in isolated blood-vessels of the cerebral cortex and hippocampus. In addition, p-NFkB was increased only in the cerebral cortex versus the intact group. Sleep loss increased the expression of the A2A adenosine receptor only in isolated microvessels of the hippocampus. Both regions presented an increase in BBB permeability to Na-fluorescein, Evans blue and rhodamine 123. In conclusion, sleep loss induces a pericyte detachment from the capillary wall, which is related to a decrease in the expression of tight junction proteins and an increase in the BBB permeability. The mechanism that may modulate the interactions between brain endothelial cells and pericytes after sleep restriction seems to be a low-grade inflammatory status.